Towards Critical Analysis of the Political Determinants of Health; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Julia Smith (Kerman University of Medical Sciences, 2020)
The recent perspective article "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention," by Lencucha and Throw, interrogates how the dominant neoliberal paradigm restricts meaningful policy action to prevent non-communicable diseases (NCDs). It contributes an NCD perspective to the existing literature on neoliberalism and health, which to date has been dominated by a focus on HIV, gender and trade agreements. It further advances the emerging commercial determinants of health (CDoH) scholarship by calling for more nuanced analysis of how the governance of both health and the economy facilitates corporate influence in policy-making. In political science terms, Lencucha and Throw are calling for greater structural analysis. However, their focus on the pragmatic, as opposed to political, aspects of neoliberalism reflects a hesitancy within health scholarship to engage in political analysis. This depoliticization of health serves neoliberal interests by delegitimizing critical questions about who sustains and benefits from current institutional norms. Lencucha and Throw's call for greater interrogation of the structures of neoliberalism forms a basis from which to advance analysis of the political determinants of health.